In-situ synthesized nanocrystalline UO2/SiC composite with superior thermal conductivity. Issue 22 (15th November 2021) - Zhang, Dezhi; Li, Yingru; Yang, Zhenliang; Li, Bingqing; Wang, Zhiyi; Huang, Qiqi; Yan, Biaojie; Chu, Mingfu; Yu, Libing; Zeng, Rongguang; Zhang, Pengcheng; Bai, Bin; et al.
Abstract: In this study, a novel UO2 /SiC nanocomposite pellet was constructed via in-situ hydrothermal synthesis and SPS. Such method could avoid the problem of traditional mechanical mixing that could obtained the molecular level mixing during a chemical process. Using such method, SiC was dispersed uniformly in the UO2 matrix. Its thermal conductivity is significantly higher than those of UO2 pellet fabricated using hydro-thermally prepared powder and traditional UO2 pellets at both working temperature (400 °C) and near-accident temperature (1000 °C). The thermal conductivity of UO2 /SiC nanocomposite pellet increased 23.7 % over traditional UO2 and 48.9 % over UO2 pellet fabricated using hydro-thermally prepared powder at 400 °C. It also increased 33.6 % over traditional UO2 and 74.8 % over UO2 pellet fabricated using hydro-thermally prepared powder at 1000 °C. These advantages are expected to maintain high thermal conductivity of fuels, enhance heat transferring efficiency of reactors, and minimize risks of pellet failure in the entire fuel life cycle.